IMPLICATIONS OF ALTERNATIVE TREATMENT IN BREAST CANCER (CIPEEX, 2022)
BREAST CANCER IS THE MOST FREQUENT AMONG WOMEN AND RESULTS FROM A MALIGNANT NEOPLASM IN THE MAMMARY GLAND AND CAN LEAD TO METASTASIS AND EVEN DEATH. CONVENTIONAL TREATMENT USUALLY INVOLVES DRUGS, SURGERIES, IMMUNOTHERAPIES AND RADIOTHERAPIES, HOWEVER, THEY ARE LIMITED BY NEGATIVE SIDE EFFECTS, SUCH AS THE EFFECT ON HEALTHY CELLS AND THE PRODUCTION OF HEMATOPOIETIC CELLS. COMPLEMENTARY AND ALTERNATIVE MEDICINES (CAMS) HAVE BECOME INCREASINGLY POPULAR, APPEARING QUITE CLEARLY IN CANCER PATIENTS AS A SELF-MEDICATION TOOL. REGARDING THE TYPES OF TREATMENTS, THERE ARE THE SO-CALLED "CONVENTIONAL" ONES, WHICH ARE THOSE ACCEPTED BY THE MEDICAL COMMUNITY; THE SO-CALLED "COMPLEMENTARY", WHICH ARE CHARACTERIZED BY JOINT USE OF CONVENTIONAL PRACTICES AND "ALTERNATIVE" TREATMENT, WHICH IS WHAT IS USED INSTEAD OF CONVENTIONAL THERAPY. THUS, THE OBJECTIVE OF THIS WORK IS TO CORRELATE THE DEVELOPMENT OF BREAST CANCER, THE FORMS OF ALTERNATIVE TREATMENTS AND THE IMPROVEMENT OF THE PATIENTS. THE METHODOLOGY USED IS BASED ON A LITERATURE REVIEW IN THE PUBMED DATABASES, WITH THE DESCRIPTORS "MEDICINE", "ALTERNATIVE", "COMPLEMENTARY", "CANCER", "BREAST", "MEDICINAL PLANTS". IN CONCLUSION, THE EXTRACT ETHANOLIC STUDY OF FRESH LEAVES INDUCED A PROGRAMMED CELL DEATH BY HUMAN BREAST CANCER MDA-MB-231 VIA ENDOPLASMIC RETICULUM AND OXIDATIVE STRESS BY THE ACTIVATION OF EXTRINSIC AND INTRINSIC SIGNALING PATHWAYS.
Keywords: Medicine. Alternative. Cancer. Mama. Plants.